2016
DOI: 10.2147/copd.s103335
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation errors due to device switch in patients with chronic obstructive pulmonary disease and asthma: critical health and economic issues

Abstract: BackgroundDifferent inhalation devices are characterized by different techniques of use. The untrained switching of device in chronic obstructive pulmonary disease (COPD) and asthma patients may be associated with inadequate inhalation technique and, consequently, could lead to a reduction in adherence to treatment and limit control of the disease. The aim of this analysis was to estimate the potential economic impact related to errors in inhalation in patients switching device without adequate training.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 24 publications
3
52
0
3
Order By: Relevance
“…However, when actually compared with reports from other countries, our study found similar mean savings with interventions in the Portuguese scenario, which reinforces the generalizability of our findings. In addition, most previous reports used a standard cost‐effectiveness model, which was also our approach . However, similarly to these reports, we also found a very wide range of plausible values, which could be due to uncertainty of estimation of exacerbation costs and difficulty in establishing the true costs of intervention programs.…”
Section: Discussionsupporting
confidence: 63%
“…However, when actually compared with reports from other countries, our study found similar mean savings with interventions in the Portuguese scenario, which reinforces the generalizability of our findings. In addition, most previous reports used a standard cost‐effectiveness model, which was also our approach . However, similarly to these reports, we also found a very wide range of plausible values, which could be due to uncertainty of estimation of exacerbation costs and difficulty in establishing the true costs of intervention programs.…”
Section: Discussionsupporting
confidence: 63%
“…Although the included studies did not perform any cost‐effective analysis or report adverse effects of the interventions, the potential benefits may outweigh the risks, which also favors regular inhaler education. Several studies have highlighted these aspects …”
Section: Discussionmentioning
confidence: 99%
“…We found inconsistent results in clinical control and quality of life, but overall, interventions seem to significantly reduce exacerbation rates. This is particularly relevant for health economics, and several studies have shown positive, cost‐effective associations in this field …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pengiriman obat melalui nebulizer ke paru-paru sangat cepat, sehingga aksinya lebih cepat daripada rute lainnya. Pengobatan lewat nebulizer ini lebih efektif dari obat oral karena langsung dihirup masuk ke paru-paru, sehingga dosis yang dibutuhkan pun lebih kecil 16 .…”
Section: Gambaran Penggunaan Antibiotikunclassified